Frontiers of Engineering : Reports on Leading-Edge Engineering from the 2010 Symposium (National Academies Press, 2011)
This volume highlights the papers presented at the National Academy of Engineering's 2010 U.S. Frontiers of Engineering Symposium. Every year, the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and technical work. The 2010 symposium was held September 23 - 25, and hosted by IBM at the IBM Learning Center in Armonk, New York. Speakers were asked to prepare extended summaries of their presentations, which are reprinted here. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work."--Publisher's description.